2019
DOI: 10.1109/lmag.2018.2886339
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Position Sensing and Force Feedback for a Magnetic Stylus With an Interactive Display

Abstract: This paper describes the design, implementation, validation, and demonstration of an electromagnetic system which can be incorporated into a graphical display to provide computer-controlled planar feedback forces on the tip of a stylus or fingertip-mounted magnet held near the display surface, according to the magnet position and virtual fixtures implemented in software. An array of magnetometer sensors is used to detect the position of the magnet, while a pair of box-shaped coils behind the display produces f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Possibly the closest related work to ours are the Omnimagnet by Petruska et al [29] and its variants [30]. Like ours, the system generates an omni-directional magnetic field in the surroundings of the actuator.…”
Section: A Related Workmentioning
confidence: 71%
“…Possibly the closest related work to ours are the Omnimagnet by Petruska et al [29] and its variants [30]. Like ours, the system generates an omni-directional magnetic field in the surroundings of the actuator.…”
Section: A Related Workmentioning
confidence: 71%
“…The shortcoming of passive magnets can be addressed using electromagnetism and computational control of magnetic forces. Two-dimensional arrays of electromagnets can be combined with passive magnets that are worn [58,63,60,2,8,6,9] or embedded in tools and interactive objects [28,43,57]. The actuation area can be increased by attaching an electromagnet to a biaxial linear stage [32,33].…”
Section: Electromagnetic Haptic Feedbackmentioning
confidence: 99%
“…The field produced by the actuator is modeled and subtracted from the measured data to obtain the field of the capsule. A magnetic position sensing and force feedback generated by a single electromagnetic coil for a magnetic stylus using an array of 16 × 16 Hall effect sensors have been developed by Berkelman [2018]. They have observed that the field generated by the coil interferes with the field generated by the stylus, and results in position estimation error.…”
Section: Introductionmentioning
confidence: 99%